Has Regionalism Peaked? The Latin American Quagmire and its Lessons - Malamud, Andrés; Gardini, Gian Luca (International Spectator, 2012)
Since 1960, Latin American attempts at regionalism have undergone distinct phases. More notably, they have tended to diverge across space, gradually giving birth to separate blocs that seem to be tearing South, Central and North America apart. Additionally, within and across these regions several overlapping projects coexist. This article focuses on the dynamics of segmented and overlapping regionalism in order to describe what they look like, analyse how they articulate with one another, and explain why member states have pushed for such a messy outcome. This situation, linked to the evolution of the global context, might be indicating that regionalism in Latin America has reached its peak, beyond which it may be difficult to achieve further progress. Two conclusions are elicited: first, economic integration is becoming a geographically diffused phenomenon rather than a regional one; second, regionalism is still a compelling foreign policy but its causes, goals and outcomes are no longer what they used to be. © 2012 Copyright Taylor and Francis Group, LLC.
WiSo-Import:2015-03-26:5131
Keywords: Regionalism; Latin America